191 CURRENT STATUS OF ESOPHAGECTOMY IN JAPANESE NATIONAL CLINICAL DATABASE. (17th September 2021) - Kakeji, Yoshihiro; Takahashi, Arata; Hasegawa, Hiroshi; Takiguchi, Gosuke; Oshikiri, Taro; Nakamura, Tetsu; Miyata, Hiroaki; Kitagawa, Yuko
Abstract: : The Japanese National Clinical Database (NCD) started its data registration since 2011, has grown up to a large nationwide database covering more than 95% of the surgeries performed by regular surgeons in Japan. The NCD grew rapidly harvesting over 11 million cases data between 2011 and 2018 from more than 5, 000 facilities. Methods: In this period, the surgeries of the esophagus were performed for 70, 528 cases. In 2018, 93.8% of surgeries were performed at certified institutions, and 94.7% did with the participation of the board-certified surgeon. The board-certified surgeons operated 75.2% of the surgeries. Results: Esophagectomy was performed for 47, 055 patients in eight years. In 2018, 23.3% of the cases were 75 years old or more. Postoperative complications of Clavien Dindo classification grade III or higher occurred in 22.9% of all. As the patients have been getting older, the morbidities have been increasing. However, the mortalities have been kept at a low level. Postoperative 30-day and 90-day mortalities were 0.9% and 1.9%, respectively. The rates of endoscopic surgery have been increasing year by year, especially high in esophagectomy, which was 61.0% in 2018. Conclusion: A risk-adjusted analysis based on nationwide data allows personnel to establish and provide feedback on the risks that patients face before undergoing a procedure. The risk calculator for eight main procedures are available on the websites of the hospitals that are a part of NCD. Nationwide this database is surely expecting to ensure the quality of board certification system and surgical outcomes in gastroenterological surgery.